Study on computational methods applied to modelling of pulse shaper in split-Hopkinson bar - Baranowski, P.; Janiszewski, J.; Malachowski, J. (Archives of Mechanics, 2014)
The paper presents a possibility of numerical modelling of a copper shaper utilized in an SHPB device with additional attention paid to the proper bar-shaper interaction simulation. The pulse shaper was modelled with the use of three methods available in the commercial code, i.e., applying typical finite Lagrangian elements, meshless smoothed particle hydrodynamics (SPH) method and multi- material arbitrary Lagrangian–Eulerian (MM-ALE) formulation. Additionally, the authors performed a mesh (particles) sensitivity study and the assessment of its influence on the obtained incident pulse characteristics. Consequently, the results obtained from all numerical analyses were compared and validated with the experimental ones with a particular attention given to the shape of the incident pulse and copper shaper deformation. The paper describes also the investigation of a relationship between the contact (coupling) force and the impulse shape.